2019
DOI: 10.1080/09205063.2019.1570433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adipose stem cells sources from various locations of rat body for their application for seeding on polymer scaffolds

Abstract: Adipose tissue yields adult adipose stem cells (ASCs) in large quantities via less-invasive methods. These cells are of interest owing to their modulating properties and paracrine activities, which can be harnessed in regenerative medicine. Many studies on the use of rat fat tissue in an autologous animal model have been conducted; however, the different locations to obtain stromal vascular fraction of rat fat depots have not been fully characterized. The purpose of the current study was to identify optimal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The expression rate of CD73, CD90, and CD105 was lower than that in human MSCs presented by the International Society of Cell therapy (ISCT) 31 . However, this has been reported a number of times in rats because of different species, isolation, culture methods, and location of fat 12 , 32 , 33 .
Figure 1 Characteristics of cultured rat adipose tissue-derived stem cells (ADSCs).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression rate of CD73, CD90, and CD105 was lower than that in human MSCs presented by the International Society of Cell therapy (ISCT) 31 . However, this has been reported a number of times in rats because of different species, isolation, culture methods, and location of fat 12 , 32 , 33 .
Figure 1 Characteristics of cultured rat adipose tissue-derived stem cells (ADSCs).
…”
Section: Resultsmentioning
confidence: 99%
“…Another disadvantage is the lack of previous research on limbal MSCs compared with research on MSCs derived from adipose tissue or BM. ADSCs are abundant in the human body, making them a potential material for wound healing and tissue engineering with low risks in terms of cell acquisition and easy processing 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our previous work [18] in an animal model showed that ASCs seeded into PCL and PCL + 5% TCP promoted proliferation, adhesion and osteogenic differentiation. The osteogenic assay showed that ASCs seeded on the PCL scaffold that were cultured in osteogenic medium presented significantly higher alkaline phosphatase levels during a 14-day culture period compared with ASCs cultured in the control medium (undifferentiated ASCs).…”
Section: Discussionmentioning
confidence: 95%
“…We observed that seeded ASCs adhered to the surface and migrated into scaffolds that were cultured for up to 21 days, as confirmed by DAPI staining. Moreover, the metabolic activity assessed via the MTS proliferation assay demonstrated the increase in proliferation after the 21st day of culture of ASCs on PCL [18]. However, the complete molecular process of ASC differentiation during osteogenesis and the mechanism of their cell-specific uptake remains to be fully characterized in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation